Inhibition Mechanism of Catechin, Resveratrol, Butylated Hydroxylanisole, and Tert‐Butylhydroquinone on Carboxymethyl 1, 2‐Dipalmitoyl‐sn‐Glycero‐3‐Phosphatidylethanolamine Formation. Issue 8 (17th July 2019) - Han, Lipeng; Lin, Qingna; Liu, Guoqin; Han, Dongxue; Niu, Li; Su, Dongxiao
Abstract : Abstract: It is important to inhibit the food‐derived, potentially hazardous chemical glycated lipids by natural products. A model system was established and the products are identified to study the inhibitory mechanism of four types of catechin, resveratrol (RES), and the synthetic antioxidants butylated hydroxylanisole (BHA) and tert‐butylhydroquinone (TBHQ) on the formation of carboxymethyl 1, 2‐dipalmitoyl‐sn‐glycero‐3‐phosphatidylethanolamine (CM‐DPPE) by determining hydroxyl radical (OH·), Amadori‐1, 2‐dipalmitoyl‐sn‐glycero‐3‐phosphatidylethanolamine (Amadori‐DPPE) and glyoxal (GO). The results show that the inhibitory rates of catechin and RES on the content of CM‐DPPE in the model system are higher than those of BHA and TBHQ. There are at least two inhibitory mechanisms of antioxidants on CM‐DPPE. (1) Antioxidants scavenge OH·, which blocks the process of Amadori‐DPPE oxidation to form CM‐DPPE. (2) Antioxidants trap GO, which blocks the reaction between GO and DPPE to form CM‐DPPE. This research will reveal the inhibitory mechanisms of natural antioxidants on glycated lipids from the aspect of scavenging OH· and trapping GO. Practical Application: Food manufacturers should pay attention on the production of glycated lipids in food processing. This study will provide the theoretical basis for the use of natural products to inhibit the formation of food‐derived glycated lipids. Natural products, such as catechin and resveratrol, can substitute chemical synthesis antioxidants, such as butylated hydroxylanisole and tert‐butylhydroquinone, in food processing, which inhibit the formation of glycated lipids.